If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4 + -1x) = 5 + 4x (4 * 3 + -1x * 3) = 5 + 4x (12 + -3x) = 5 + 4x Solving 12 + -3x = 5 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 12 + -3x + -4x = 5 + 4x + -4x Combine like terms: -3x + -4x = -7x 12 + -7x = 5 + 4x + -4x Combine like terms: 4x + -4x = 0 12 + -7x = 5 + 0 12 + -7x = 5 Add '-12' to each side of the equation. 12 + -12 + -7x = 5 + -12 Combine like terms: 12 + -12 = 0 0 + -7x = 5 + -12 -7x = 5 + -12 Combine like terms: 5 + -12 = -7 -7x = -7 Divide each side by '-7'. x = 1 Simplifying x = 1
| k/15=18 | | 5.1+1.9x=2.9x | | 3(3x+1)=8(x+1) | | 17-5x=3x+1 | | 2+3x=58 | | 2x-2+x=4+5 | | 18-4h=-10-4h | | 6x^2y^2-52xy^2-210y^2=0 | | 12-6x=9-7x | | 2x^2=4xs | | 2(w-3)+7=1-2w | | 4-x=x | | x^5+x^2+x=0 | | 8x+4=5(x+2) | | 9.40dm=hm | | X-2x=3x-20 | | 6(7+2x)-8x-(y+4)=12 | | 7x+8-x+7=3x+24 | | (x-3)2=15 | | -24=t-29 | | 40-13x=1 | | x^2-4x+6y+10=0 | | 8.5(13x-27)=-119 | | 2(1y-4)=-4y+10 | | 2(3x+9)=-36 | | 36z^2+9z+15=0 | | -11=2+y | | 5(u+4)=9u+32 | | 12x^2=4x | | 24+a=-14 | | 6-6x=10-8x | | -8x+95=-425 |